If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 2x + -60 = 48 Reorder the terms: -60 + 4x + 2x = 48 Combine like terms: 4x + 2x = 6x -60 + 6x = 48 Solving -60 + 6x = 48 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '60' to each side of the equation. -60 + 60 + 6x = 48 + 60 Combine like terms: -60 + 60 = 0 0 + 6x = 48 + 60 6x = 48 + 60 Combine like terms: 48 + 60 = 108 6x = 108 Divide each side by '6'. x = 18 Simplifying x = 18
| 2p-10-2=12-p-p | | r^3+3r^2=0 | | v+1-2v=4 | | 3n+15=7n-1 | | 4+3n+2=-9 | | y=2cos(3x+1) | | -4=2x+x | | 4n+8=5n-2 | | 4*log(x-9)=3 | | -1+7x=-186 | | 7e^9t=11e^8t | | 15=-6n+3n | | -7r=-21 | | p+6=2 | | x^4-49x^2-360=0 | | y-8=4x | | a^3+b^2=72 | | y=(3m+2n)(6m-8n) | | 2.3x-0.4=15.7 | | (3x)x=48 | | X*-6x+5=0 | | -68=-5x-8 | | x^2+v^2=y | | 5=25t+10 | | 21=-9 | | 21=9 | | 5y+x=w | | y=-sin(3.14x+1)-2 | | -4+8V=6+3v | | X^2(x-3)=320 | | y=(5x-3)(2x+1) | | -6(4d+10)+7d=-3d |